Respuesta patológica completa de pacientes con cáncer de mama HER2 positivo tratadas con quimioterapia neoadyuvante en Colombia - Mauricio Rodríguez; Diego M. González; Farah El-Sharkawy; Mileny Castaño; Jorge Madrid (Biomédica: revista del Instituto Nacional de Salud, 2023)
Introduction. Breast cancer is the most common type of cancer and the leading cause of death by cancer in women in Colombia. Approximately 15 to 20% of breast cancers overexpress HER2. Objective. To analyze the relationship between multiple clinical and histological variables and pathological complete response in patients with HER2-positive breast cancer undergoing neoadjuvant therapy in a specialized cancer center in Colombia. Materials and methods. We performed a retrospective analysis of non-metastatic HER2-positive breast cancer patients who received neoadjuvant therapy between 2007 and 2020 at the Instituto de Cancerología Las Americas Auna (Medellín, Colombia). Assessed parameters were tumor grade, proliferation index, estrogen receptor, progesterone receptor, HER2 status, type of neoadjuvant therapy, pathologic complete response rates, and overall survival. Results. Variables associated with low pathologic complete response rates were tumor grades 1-2 (OR = 0.55; 95% CI = 0.37-0.81; p = 0.03), estrogen receptor positivity (OR =0.65; 95%; CI = 0.43-0.97; p=0.04), and progesterone receptor positivity (OR = 0.44; 95% CI = 0.29-0.65; p = 0.0001). HER2 strong positivity (score 3+) was associated with high pathological complete response rates (OR = 3.3; 95% CI = 1.3-8.35; p=0.013). Five-year overall survival was 91.5% (95% CI = 82.6-95.9) in patients with pathological complete response and 73.6% (95% CI = 66.4-79.6) in patients who did not achieve pathological complete response (p = 0.001). Additionally, the pathological complete response rate was three times higher in patients receiving combined neoadjuvant chemotherapy with anti-HER2 therapy than in those with chemotherapy alone (48% versus 16%). Conclusion. In patients with HER2-positive breast cancer, tumor grade 3, estrogen receptor negativity, progesterone receptor negativity, strong HER2 positivity (score 3+), and the use of the neoadjuvant trastuzumab are associated with higher pathological complete response rates.